2001
DOI: 10.3109/13682820109177938
|View full text |Cite
|
Sign up to set email alerts
|

The Hanen Parent Programme: A Parent's Perspective

Abstract: In 1997 Salford Community Healthcare Trust embarked on a research project (funded by NHS Executive North West Region) to investigate how viable the Hanen Parent Programme (HPP) (Manolson 1992) was in terms of its effectiveness and suitability for an inner-city UK population in comparison with clinic-based, direct intervention. An important component of that research project involved exploring the parents' perceptions of the therapy they had undertaken. In this paper are summarised the areas in which there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 4 publications
8
30
0
Order By: Relevance
“…It also suggests that ITTT can be seen as an ‘extra’ to usual therapy by providers and service users and furthermore, parent training may be outside parents' concepts of speech and language therapy. This will require them to shift in their thinking as well as rearrange their usual family activities in order to attend (Baxendale et al . 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It also suggests that ITTT can be seen as an ‘extra’ to usual therapy by providers and service users and furthermore, parent training may be outside parents' concepts of speech and language therapy. This will require them to shift in their thinking as well as rearrange their usual family activities in order to attend (Baxendale et al . 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have sought parental views about the outcomes of a speech-language intervention (e.g. Girolametto et al 1993, Baxendale et al 2001. Using a qualitative research paradigm, Glogowska and Campbell (2000) showed that determining parents' views contributed to the evidence base both in highlighting differences between SaLTs' and parents' perceptions of the intervention process and in understanding the acceptability of an early language intervention.…”
Section: Introductionmentioning
confidence: 99%
“…only measured satisfaction retrospectively. This should be considered in light of Baxendale et al .’s () qualitative study of parents’ perceptions of HPs that reported parents had a prior expectation that their child would receive direct therapy and were resistant to engaging with an indirect model. Despite this initial expectation, once parents experienced a model of service with more parental involvement, they were satisfied with the HP service.…”
Section: Discussionmentioning
confidence: 99%